Evaluation of fine needle aspiration cytology among lymphadenopathy patients in Ambedkarnagar, Uttar Pradesh, India - Ikram, Arshad; Mahmood, Syed Esam (International Journal of Advances in Medicine, 2017)
Background: Surgical fine needle aspiration cytology is most popular diagnostic aid in patients with lymphadenopathy. Methods: This one year observational study comprised of aspirate collected from lymph nodes of patients attending Mahamaya Rajkiya Allopathic Medical College and Hospital, Ambedkarnagar, Uttar Pradesh, India. Fine needle aspiration was performed in all the patients and slides were stained with H and E, PAP and Ziehl Neelsen stains. SPSS was used for data analysis. Fischer’s Exact test was applied. Results: Out of the 51 patients, the most common site of lymph node aspirated was cervical (72.5%). A higher proportion of cases were diagnosed as chronic nonspecific lymphadenitis (23.5%) followed by granulomatous abscess (23.5%), tubercular lymph node (21.6%) and reactive (17.6%). A significant association found between FNAC diagnosis and age was found (p≤ 0.05). Conclusions: FNAC is a simple and useful procedure in patients with lymphadenopathy.